Significance of PD1 Alternative Splicing in Celiac Disease as a Novel Source for Diagnostic and Therapeutic Target - Ponce de León, Candelaria; Lorite, Pedro; López-Casado, Miguel Ángel; Barro, Francisco; Palomeque, Teresa; Torres, María Isabel (Frontiers in Immunology, 2021)
Background We have focused on the alteration of the PD-1/PD-L1 pathway in celiac disease and discussed the roles of the PD1 pathway in regulating the immune response. We explored the idea that the altered mRNA splicing process in key regulatory proteins could represent a novel source to identify diagnostic, prognostic, and therapeutic targets in celiac disease. Methods We characterized the PD1 mRNA variants’ profile in CD patients and in response to gluten peptides’ incubation after in vitro experiments. Total RNA from whole blood was isolated, and the coding region of the human PD-1 mRNA was amplified by cDNA PCR. Results PCR amplification of the human PD-1 coding sequence revealed an association between the over-expression of the sPD-1 protein and the PD-1Δex3 transcript in celiac disease. Thus, we have found three novel alternative spliced isoforms, two of which result in a truncated protein and the other isoform with a loss of 14 aa of exon 2 and complete exon 3 (Δ3) which could encode a new soluble form of PD1 (sPD-1). Conclusions Our study provides evidence that dietary gluten can modulate processes required for cell homeostasis through the splicing of pre-mRNAs encoding key regulatory proteins, which represents an adaptive mechanism in response to different nutritional conditions.